1991
DOI: 10.1161/01.atv.11.4.903
|View full text |Cite
|
Sign up to set email alerts
|

Dietary eicosapentaenoic acid and docosahexaenoic acid from fish oil. Their incorporation into advanced human atherosclerotic plaques.

Abstract: The incorporation of fatty acids from dietary fish oil was measured in obstructive atherosclerotic plaques removed from 11 patients fed fish oil, rich in &>-3 fatty acids, for 6-120 days before a planned arterial endarterectomy. The fatty acids of plasma and atheroma were analyzed with special reference to docosahexaenoic acid (DHA, 22:6) and eicosapentaenoic acid (EPA, 20:5), the principal &>-3 fatty acids offish oil. The o>-3 fatty acid content increased greatly in plasma from 0.9% of fatty acids to 14.8% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…Rapp et al found substantial incorporation of EPA and DHA into plaque lipids following consumption of a very high dose of fish oil (48-64 g/day providing 16-21 g EPA + DHA/day). 31 In contrast, 2 other studies using considerably lower doses of EPA and DHA (0.81 g EPA and 0.675 g DHA/day) found significantly higher levels of EPA in atherosclerotic plaques than DHA. 26,32 Moreover, plaques from patients treated with fish oil had fewer thin fibrous caps and signs of inflammation, with more plaques containing thick fibrous caps, no signs of inflammation, 26 and lower levels of inflammatory agents and mRNA for matrix metalloproteinases (MMP-7 and -12), interleukin-6, and intercellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 88%
“…Rapp et al found substantial incorporation of EPA and DHA into plaque lipids following consumption of a very high dose of fish oil (48-64 g/day providing 16-21 g EPA + DHA/day). 31 In contrast, 2 other studies using considerably lower doses of EPA and DHA (0.81 g EPA and 0.675 g DHA/day) found significantly higher levels of EPA in atherosclerotic plaques than DHA. 26,32 Moreover, plaques from patients treated with fish oil had fewer thin fibrous caps and signs of inflammation, with more plaques containing thick fibrous caps, no signs of inflammation, 26 and lower levels of inflammatory agents and mRNA for matrix metalloproteinases (MMP-7 and -12), interleukin-6, and intercellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 88%
“…Supplementation studies have shown that EPA and DHA are incorporated into the lipids of advanced atherosclerotic plaques in man [24], and it is possible that a reduced expression of MHC class II molecules might inhibit the antigen-presenting function of the local macrophages, thereby prolonging, if not preventing, lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…Media were removed from semiconfluent monolayers (ϳ75%) and replaced with Hanks' buffer (37°C, 10 ml) containing HEPES, 10 mM, pH 7.4, and [1-14 C]DHA (55 mCi/mmol, American Radiolabeled Chemicals, Inc., 10 M), or unlabeled C22:6 (ϳ10 M, Oxford Biomedical Research) was added in EtOH (5-10 l). Cells were placed in an incubator with an atmosphere of 5% CO 2 at 37°C for 90 min, and aliquots (100 l) were removed at 30-min intervals and analyzed by scintillation counting to determine cellular [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]DHA. At 90 min, buffer was removed and cells were washed with Hanks' buffer (10 ml, 37°C).…”
Section: Methodsmentioning
confidence: 99%